2021
DOI: 10.3390/ijerph18179218
|View full text |Cite
|
Sign up to set email alerts
|

School Teachers’ Self-Reported Fear and Risk Perception during the COVID-19 Pandemic—A Nationwide Survey in Germany

Abstract: With the coronavirus disease 2019 (COVID-19) cases peaking and health systems reaching their limits in winter 2020/21, schools remained closed in many countries. To better understand teachers’ risk perception, we conducted a survey in Germany. Participants were recruited through various associations and invited to take part in a cross-sectional COVID-19-specific online survey. Descriptive statistical analysis was performed. Factors associated with teachers’ fears of contracting the severe acute respiratory syn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
4
16
0
Order By: Relevance
“…Interestingly, the results of the multivariate logistic regression model revealed that having received this vaccination for fear of getting the disease was more likely to be indicated by the respondents of a younger age, those with at least one chronic medical condition, those more concerned about the severity of COVID-19, and those with a higher trust in the information received on the vaccination. The higher fear among those of a younger age parallels other observations in this geographic area [5] and worldwide [21][22][23]. A possible explanation is that younger people are more likely to spend time socializing with others and to be engaged in pleasant activities and, therefore, they perceive to be at higher risk of getting the disease.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, the results of the multivariate logistic regression model revealed that having received this vaccination for fear of getting the disease was more likely to be indicated by the respondents of a younger age, those with at least one chronic medical condition, those more concerned about the severity of COVID-19, and those with a higher trust in the information received on the vaccination. The higher fear among those of a younger age parallels other observations in this geographic area [5] and worldwide [21][22][23]. A possible explanation is that younger people are more likely to spend time socializing with others and to be engaged in pleasant activities and, therefore, they perceive to be at higher risk of getting the disease.…”
Section: Discussionsupporting
confidence: 76%
“…At the beginning of 2022, vaccination coverage among educational staff was very high. In December 2021, vaccination coverage among adolescents (12–17 years) had reached more than 50%, and immunisations of children (aged 5–11 years) had started [ 13 , 20 - 22 ]. At the same time, the highly transmissible and possibly less virulent SARS-CoV-2 Omicron variant of concern (B.1.1.529 of the Phylogenetic Assignment of Named Global Outbreak (Pango) lineage designation), is causing very high infection activity, and the emergence of further variants cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In this study teachers who were female, had children, and had chronic illness or cared for those with chronic illness had higher levels ( Santamaría et al., 2021 ). Specific stressors have included COVID-19 related anxiety and contagion fears, and associated with vaccination intention and resistance to school re-opening, with students being seen as the main vector of infection ( Weinert et al., 2021 ). Others studies have highlighted anxiety regarding new or additional teaching demands, degree of administrative support, and COVID-19 related stress linked to job insecurity, with fears of layoff following the economic downturn ( Pressley, 2021 a; Aunión & Romero, 2020 ).…”
Section: Introductionmentioning
confidence: 99%